If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(9n + -4) = 2(11 + -8n) Reorder the terms: -2(-4 + 9n) = 2(11 + -8n) (-4 * -2 + 9n * -2) = 2(11 + -8n) (8 + -18n) = 2(11 + -8n) 8 + -18n = (11 * 2 + -8n * 2) 8 + -18n = (22 + -16n) Solving 8 + -18n = 22 + -16n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '16n' to each side of the equation. 8 + -18n + 16n = 22 + -16n + 16n Combine like terms: -18n + 16n = -2n 8 + -2n = 22 + -16n + 16n Combine like terms: -16n + 16n = 0 8 + -2n = 22 + 0 8 + -2n = 22 Add '-8' to each side of the equation. 8 + -8 + -2n = 22 + -8 Combine like terms: 8 + -8 = 0 0 + -2n = 22 + -8 -2n = 22 + -8 Combine like terms: 22 + -8 = 14 -2n = 14 Divide each side by '-2'. n = -7 Simplifying n = -7
| 2x^(2/3)-x^(1/3)=6 | | -4v+2=2(v+7) | | -8=2(x+6) | | 5x+3y=371 | | w+10=3w-10 | | 4(-5+7a)=26+5a | | 9/28•19/54 | | (14n/3)=8(n-14) | | -25/28•(-21) | | 2X-(5X+9)=8-3X | | 1+6(x-4)=2-8(x-9) | | (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) |